The economy of the Urartian Kingdom - ÇİFÇİ, ALİ (Peeters Publishers, 2021)
After an opening review and critique of Soviet and Western and Turkish scholars (some of whom were influenced by Marxism) and their interpretations of the socioeconomic structure and nature of Urartian society, this chapter goes on to examine briefly the topography, hydrology, climate and ecology of the Urartian lands before turning to mainstays such as agriculture (increasingly important), animal husbandry and metallurgy, and trade and the spoils of war. A lengthy synthetic discussion then ensues within a framework of the three phases of socio-economic and political development identified by the author (expansionist, transitional and crisis) and the general trend to greater centralism. The discussion includes an examination of the Sarduri II’s inscription of Hazine Kapısı/Analıkız at Van Kalesi and how particular terminology should be and has been interpreted.
Keywords: Sosyal ve Beşeri Bilimler; Tarih; Eskiçağ Tarihi; Anadolu Medeniyetleri Ve Kültür Mirası Yönetimi; Arkeoloji ve Sanat Tarihi; Social Sciences and Humanities; History; Ancient History; Heritage Management for Anatolian Civilizations and Culture; Archaelogy and History of Art; Sanat ve Beşeri Bilimler (AHCI); Sosyal Bilimler (SOC); Sanat ve Beşeri Bilimler; ARKEOLOJİ; TARİH; Arts & Humanities (AHCI); Social Sciences (SOC); ARTS & HUMANITIES; ARCHAEOLOGY; HISTORY; Arkeoloji; Arkeoloji (sanat ve beşeri bilimler); Sosyal Bilimler ve Beşeri Bilimler; Archeology; Archeology (arts and humanities); Social Sciences & Humanities